The Effect Of Childbirth Education On Primigravida Anxiety Levels - Umami, Siti Fithrotul; Idayanti, Titiek; Virgia, Vera (Jurnal MIDPRO, 2022)
Most of the third trimester primigravida mothers who will face the birth process experience various anxiety, this can be caused by several factors, including the lack of knowledge and information about the correct delivery process, the provision of education that must be done by health workers also greatly affects the level of anxiety of primigravida mothers in facing the labor process. The purpose of this study was to analyze primigravida anxiety levels in facing the labor process in terms of education at KIA room in Pratama Eka Medika Pungging Clinic – Mojosari . The research design used is Pre Experimental with a research design one group Pretest-Posttest. The population in this study was all primigravida mothers who came to check at Pratama Eka Medika Pungging Clinic - Mojosari. The sampling technique used was consecutive sampling and a total sample of 35 respondents was obtained. The free variable in this study is the education of the labor process. The variable bound to this study is the level of primigravida anxiety in the face of the labor process. Data analysis using Wilcoxon statistical test. The results showed that Wilcoxon Asymp statistical test results. Sig. (2-tayled) is worth 0.000 < 0.05, then it can be concluded that "Ha is accepted".meaning that there is a difference in the level of anxiety before treatment and after being given treatment. Health workers should be able to pay attention to the importance of giving birth education starting at the beginning of the third trimester of pregnancy. Education can help provide mothers with knowledge and understanding of the physiological delivery process so that mothers can avoid excessive anxiety before facing the birth process.